An efficient fault tolerant control scheme for Euler-Lagrange systems - Leal-Leal, Ivon E.; Alcorta-Garcia, Efrain (Zielona Góra: Uniwersytet Zielonogórski)
Every closed-loop system holds a level of fault tolerance, which could be increased by using a fault tolerant control (FTC) scheme. In this paper, an efficient FTC scheme for a class of nonlinear systems (Euler?Lagrange ones) is proposed, which guarantees high performance and stability in a faulty system. This scheme was designed on the basis of a cascade control structure in which the inner loop is the closed-loop system and the external loop is the FTC, a generalized proportional integral (GPI) observer-based controller, which manages the fault tolerance level increment.
Keywords: cascade structure; Euler-Lagrange systems; FTC scheme; GPI observer-based controller